2002
DOI: 10.1117/12.464462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhomogeneous line broadening on electromagnetically induced transparency (EIT) and slow group velocity

Abstract: We show for the first time an explicit expression of the linewidth of an EIT resonance in an inhomogeneously broadened three-level A system, and the conditions for the dependence of the linewidth on a driving field strength.Both gaseous systems with the Doppler effect and solid media in which inhomogeneity of the crystalline fields results in a broad distribution of atomic center frequencies are considered. We find two extreme cases: in one extreme the linewidth of EIT resonance is proportional to the intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…More elaborate cases, when the finite inhomogeneous bandwidth has to be taken into account explicitly, have been considered in the context of EIT. Several limiting cases have been identified to reduce the effects of inhomogeneous broadening . It has been further shown that the V-scheme is less vulnerable, while control field strength is a crucial factor in maintaining the controllable bandwidths of the EIT resonances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More elaborate cases, when the finite inhomogeneous bandwidth has to be taken into account explicitly, have been considered in the context of EIT. Several limiting cases have been identified to reduce the effects of inhomogeneous broadening . It has been further shown that the V-scheme is less vulnerable, while control field strength is a crucial factor in maintaining the controllable bandwidths of the EIT resonances.…”
mentioning
confidence: 99%
“…Several limiting cases have been identified to reduce the effects of inhomogeneous broadening. 31 It has been further shown that the V-scheme is less vulnerable, 32 while control field strength is a crucial factor 33 in maintaining the controllable bandwidths of the EIT resonances. While larger inhomogeneous broadening is rather detrimental in the case of the pure frequency domain experiments, such as EIT, it it is more prone to benefit pure time-domain photon echo experiments.…”
mentioning
confidence: 99%